The Secret Behind Blue Curcumin:: DNA Primers in Action - Gunawan, Gracecielo Isaiah Poetra Andriyanto; Rahmawati, Dewi (BIODIVERS - BIOTROP Science Magazine, 2025)
Ever heard of PCR? It is a laboratory technique that copies tiny DNA pieces in a fast manner, but it needs a ‘primer’ (like a GPS) to mark where to start. PCR method helps in studying Indonesia’s blue curcumin (Curcuma aeruginosa). By picking the right primers, genetic tags for genes like ITS1, rbcL, or matK, can help scientists in copying key DNA segments, which is known as. DNA barcoding: using genes as a plant’s ‘ID card’ for identification. Here we show how finding these primers will aid to the conservation and science-based herbal medicine. Small tools, big impact on biodiversity!